PENGARUH WAKTU REAKSI DAN RASIO MOL ASAM LINOLEAT DENGAN ISOPROPANOL PADA SINTESA PLASTISIZER ISOPROPIL LINOLEAT - Nirwana -; Irdoni HS -; Joni Miharyono (Jurnal Riset Kimia, 2015)
Diversity of palm oil product in Indonesia is still limited, therefore it is needed to take an advantage of the development of downstream product of crude palm oil by esterification reaction. Esterification reaction is a reaction between carboxylic acid and alcohol to form ester. One of the emerging downstream product fatty acid alkyl ester is plasticizer. Plasticizer is an additive compound added to polymer to improve flexibility and workability. The purpose of this research was conducted to study the effect of reaction time and mole ratio and identify product of plasticizers isopropyl linoleic. In this research, plasticizer was synthesized by esterification of linoleic acid and isopropanol, using activated natural zeolite catalyst. The process was done with a variation of reaction time (4, 6, and 8 hours) and mole ratio (1: 6, 1: 9, and 1:12), with reaction temperature at  80 °C,  stirring speed at 200 rpm and 15% of composition of linoleic acid based catalyst as fixed variables. From the analysis of the results showed that the esterification reaction time and mole ratio affect the product conversion. The best operating condition obtained  in this research was 4 hours of reaction time and 1:12 of mole ratio which resulted the conversion of reaction was 67.09%. Characteristics of plasticizer produced from this research were viscosity (at 20 °C) 2.405 to 2.803 mPa.s and Specific Gravity (at 20 °C) from 0.863 to 0.872.